SecureTCG: a lightweight cheating‐detection protocol for P2P multiplayer online trading card games. Issue 12 (17th January 2014) - Simplicio, Marcos A.; Santos, Mateus A.S.; Leal, Rodrigo R.; Gomes, Marco A.L.; Goya, Walter A.
ABSTRACT Online gaming is today a very lucrative market, with millions of users all around the globe. At the same time, the increasing popularity and complexity of such games implies the need of deploying cheating‐detection mechanisms for ensuring the continuous interest of honest users in playing. The development of secure and efficient solutions for online games is, however, a challenging issue. This is especially true in P2P environments, in which the lack of a central trusted entity monitoring the game greatly facilitates the activity of malicious players. Aiming to tackle this issue, this paper presents SecureTCG, a protocol for detecting cheating attempts in P2P multiplayer card games where the players use their own decks to play, such as the so‐called trading card games. In summary, SecureTCG allows the multiple players participating in a trading card game match to detect cheating attempts as soon as they are made and without the intervention of third parties, supports multiple players and different game styles, displays tolerance to players' dropouts during a match, prevents collusion among any number of players, provides (optional) after‐match auditability mechanisms, and has a reduced computational cost. Copyright © 2014 John Wiley & Sons, Ltd.